The Opportunity Cost in Health Care: Low Cost High Value - Querci, Elena; Gazzola, Patrizia (European Scientific Journal, ESJ, 2017)
There is a need to innovate with new management tools to be disseminated both in the public health and in the private sector. The ways to contain health care expenditure, normally involve a decrease in the quality of services. Some of the measures are commonly adopted patient co-pay schemes, or practicing de-facto rationing, either by limiting the number of actual treatments provided in combination with long waiting lists, or carrying out consumer health campaigns focused on prevention, all with the aim of limiting the demand for public health services. Major industrialized countries have focused on reforming health care to cut costs rather than implementing policies to improve the health of their populations and thus stimulate national economic growth. Low cost-high value services are the answer firstly, to an individual’s desire for personalized health care and secondly, to the inability of the western health care systems to respond to this change. Low Cost- High Value companies are new entries in those areas of the competitive system left vacant by the welfare state and they meet the patient’s new needs to safeguard health with out of pocket payment. Often they are prime mover companies that launch innovations, invest in the development of new products and accept the risk of exploring unknown territory. The analysis of two case studies: Centro Medico Sant’Agostino and Odontosalute, highlights that the traditional health care business model and the low cost high value are significantly different in several points of their chain of values.)